2020
DOI: 10.1111/jcmm.15102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes and pathways in adrenocortical carcinoma by integrated bioinformatic analysis

Abstract: Adrenocortical carcinoma (ACC), a rare malignant neoplasm originating from adrenal cortical cells, has high malignancy and few treatments. Therefore, it is necessary to explore the molecular mechanism of tumorigenesis, screen and verify potential biomarkers, which will provide new clues for the treatment and diagnosis of ACC. In this paper, three gene expression profiles (GSE10927, GSE12368 and GSE90713) were downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Secondly, carcinogenesis and progression of tumors are the result of multi-gene dysregulation and different genes can have various effects on tumor prognosis. Although the low-expression genes identified in ACC in the present study are involved in multiple key steps of tumorigenesis and progression, their effects on prognosis may be less than the effects of high-expression genes identified in previous studies (22,59). Compared with other urologic neoplasms, ACC has a low incidence (0.7-2/million), which may lead the insufficiency of datasets and samples.…”
Section: Discussionmentioning
confidence: 56%
“…Secondly, carcinogenesis and progression of tumors are the result of multi-gene dysregulation and different genes can have various effects on tumor prognosis. Although the low-expression genes identified in ACC in the present study are involved in multiple key steps of tumorigenesis and progression, their effects on prognosis may be less than the effects of high-expression genes identified in previous studies (22,59). Compared with other urologic neoplasms, ACC has a low incidence (0.7-2/million), which may lead the insufficiency of datasets and samples.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, previous studies have not shown interactions between TOP2A and co-expression genes BUB1, CDK1, CENPF, RACGAP1, FBXO5 and BUB1B in CC. However, Guo et al (59) suggested that BUB1, CDK1, RACGAP1 and TOP2A may be involved in the tumorigenesis of adrenocortical carcinoma. Li et al (60) showed that lower expression levels of TOP2A and CENPF were associated with improved overall survival in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The genes responsible for the analyzed functional pathways were selected from Kyoto Encyclopedia for Genes and Genomes (KEGG)[ 37 ]. However, KEGG, as any other specialized software (DAVID[ 38 ], Ingenuity[ 39 ], GeneMAPP[ 40 ] etc .) to ensemble genes into functional pathways, is a text miner from trustable peer-reviewed publications that explores gene and protein expression profiles .…”
Section: Introductionmentioning
confidence: 99%